E-Government Maturity Model to Support System Dynamics in Public Policymaking - Feldiansyah Bakri Nasution; Nor Erne Nazira Bazin (IAES Indonesia Section, 2018)
In this paper, the main output of e-government is designed to assist a policymaker to create a comprehensive public policy. The policy is developed by studying the political and social issues in holistic way. System Dynamics based on Big Data from e-government infrastructure is suggested as the method for obtaining a comprehensive solution. The solution is selected from some possible scenarios by running simulation on the model of System Dynamics. The policymaker uses this solution as an input for public policymaking. Unfortunately, no E-Government Maturity Model (EMM) has given attention to incorporate Big Data and System Dynamics for Public Policymaking. In this case, a new EMM is proposed. It consists of several stages. Each stage is identified by the range of intensity or level of several criteria or indicators. Some criteria or indicators are proposed by considering technical and non-technical aspect, such as Leadership / Policy, IT Infrastructure, Information Processing (Application), Human Resources and Organization Culture. At the end of this paper, the survey is conducted to identify the current level or stage of EMM of one of government institution in Indonesia.